APPLICATION OF TRAVEL SALESMAN PROBLEM FOR OPTIMAL ORDER OF PHASES OF LIGHT CONTROLLED INTERSECTIONS (Perner's Contacts, 2011)
The article deals with determining the optimal phase sequence light controlled intersections. The introduction describes the general problems associated with the selection of the optimal phase sequence. Following the theoretical part, which describes two basic approaches to tackling tasks and using heuristic methods and using a mathematical model. The following is an application of described methods at several examples and the conclusion is an assessment of used approaches and the obtained solutions.
Keywords: traffic flow; phase; intersection; mathematical model